Visual Communication Strategies on Instagram: Analyzing The Slow Factory’s Engagement with Social-Political Issues - Sameto, Putri Merak Jingga; Sameto, Mayang Belia; Suwanda, Patra (International Journal of Multidisciplinary Research of Higher Education, 2025)
Social media has evolved into a strategic space for communicating socio-political issues to the younger generation. Visual communication design plays an important role in influencing audience engagement through the presentation of information that is concise, easy to understand, and aesthetically appealing. This study analyzed the effectiveness of visual communication strategies used by the Slow Factory Instagram account (@slowfactory) in raising issues such as the climate crisis, racial justice, colonialism, and sustainability. Using a qualitative approach through content analysis and visual observation, this study identifies that The Slow Factory can enhance the ability of young audiences to understand complex issues through structured and easily digestible visual narratives.